Analysis Of The Effect Of Leadership And Workload On Job Satisfaction In The Out Bond Division Of PT JNE Express Medan Main Branch - Gunawan, Mhd Fikri; Malikhah, Ikhah; Wakhyuni, Emi (Jurnal Fokus Manajemen, 2025)
The research analysis aims to determine whether Leadership and Workload have a positive and significant effect simultaneously on the job satisfaction of employees in the out bond division of PT JNE Express Cabang Utama Medan. The data analysis technique used is the associative research method with the help of the SPSS version 25. This study uses multiple linear regression analysis. The sample in this study was 55 respondents. Primary data collection using a questionnaire. The results of the study indicate that leadership has a positive and significant effect partially on employee job satisfaction in the outbound division of PT JNE Express Cabang Utama Medan. Workload has a positive and significant partial effect on employee job satisfaction in the out bond division of PT JNE Express Cabang Utama Medan. Leadership and Workload have a positive and significant simultaneous effect on employee job satisfaction in the out bond division of PT JNE Express Cabang Utama Medan.